Pengembangan panduan konseling CBT teknik kognitif dispute serta modeling untuk meningkatkan self-efficacy kesehatan reproduksi siswa - Tria Noviyanti; Kadek Suranata; I Ketut Dharsana (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
The aim of this study was to (1) produce the design of a counseling guide, (2) determine the validity of the contents of the guide, (3) determine the practicality of the guidebook, and (4) understand the effectiveness of the CBT Counseling, Counseling handbook with Cognitive Dispute and Modelling Techniques to Improve Self-Efficacy of Reproductive Health for Middle School Students. This research method uses research and development (R&D) with the 4D (Four D) model developed by Thiagarajan, using a questionnaire instrument. Expert testers of guide product involve five Guidance and Counseling experts. The results of this study indicates that (1) produce a CBT counseling guidebook, and (2) test the validity of the Lawshe formula for the contents of the guidebook. The results obtained from the validity test using Lawshe CVR and CVI showed that the per-item value was greater than zero (CVR>0). Furthermore, the results of the Lawshe CVI analysis obtained a score of one. Based on the data analysis, it mean that the content validity value of the guidebook product is the high, meaning it is consideres feasible to be develop.(3) the practicality test of the guidebook on the assessment of 10 guidance and counseling practitioners is declared practical (90%), (4) the effectiveness of the guidebook obtains a sig value (2- tailed) is < 0.001 or below 0.05 so that it can be said that the CBT counseling guidebook is effective in increasing students' reproductive health self-efficacy.